PENGARUH KUALITAS PELAYANAN DAN SUKU BUNGA DENGAN KEPUASAN SEBAGAI VARIABEL MODERATING TERHADAP LOYALITAS NASABAH (Studi pada Nasabah Koperasi Simpan Pinjam Sumber Makmur di Kebakkramat) - Rudi Kusdi Harto, SL Triyaningsih & Retno Susanti (Universitas Slamet Riyadi, 2016)
The purpose of this study are: 1) To analyze the significance of the influence of service quality, interest rates, and satisfaction on customer loyalty in Sumber Makmur Credit Unions in Kebakkramat. 2) To analyze the effect of moderating the influence of satisfaction on service quality and the interest rate on customer loyalty in Sumber Makmur Credit Unions in Kebakkramat. The population is all credit customers Sumber Makmur Credit Unions in Kramat kebak of the 3000 customers with a sample of 100 customers. Data analysis techniques used classical assumption test,multiple linear regression analysis, t test, F test, the coefficient of determination, and a test of the absolute value of the difference. The conclusion of each hypothesis test results show that (1) the quality of service significantly affects customer loyalty Sumber Makmur Credit Unions in Kebakkramat, as evidenced by the t test generates a probability value (0,028) < 0,05. (2) the interest rate had no significant effect on customer loyalty Sumber Makmur Credit Unions in Kebakkramat, as evidenced by the t test generates a probability value (0,318) < 0,05. (3) the satisfaction significantly affect customer loyalty Sumber Makmur Credit Unions in Kebakkramat, as evidenced by the t test generates a probability value (0,005) < 0,05. (4) satisfaction does not moderate the impact of service quality on customer loyalty Sumber Makmur Credit Unions in Kebakkramat, is evident from the test absolute value of the difference that generates a probability value (0,315) < 0,05. (5) the satisfaction does not moderate the effect of interest rates on customer loyalty Sumber Makmur Credit Unions in Kebakkramat, is evident from the test absolute value of the difference that generates a probability value (0,803) < 0,05. Based on the results of the analysis showed that satisfaction does not moderate the impact of service quality and the interest rate on customer loyalty Credit Unions Sumber Makmur in Kebakkramat, so that the position satisfaction variables more appropriate as an independent variable because a significant effect on customer loyalty Credit Unions Sumber Makmur in Kebakkramat.Keywords: service quality, interest rates, satisfaction, customer loyalty